Os impactos da modalidade do pregão eletrônico nas compras do governo do Estado do Ceará - Saraiva, Marilia Cavalcanti Leite (2012)
The purpose of this paper is to measure the impact of the introduction of Electronic Auction mode in Government Procurement Policy of the State of Ceará, seeking to verify the fact resulted in savings for the public coffers, but also estimate the speed of the completion time of processes bidding. For that we sought to establish a comparison between the savings generated by the modalities of Invitation Letter and Decision-Price in the period prior to Auction (1994/1999) and after that (2007/2010). To estimate the efficiency of electronic trading with the above methods of procurement used data obtained with the purchase of the same nature in the public state, and also research in sites, the Ministry of Planning, Budget and management and System of the Bank of Brazil. Was used for analysis, simple linear regression statistics. The proposed model used three variables: purchase price, length of stay and number of process participants, and a dummy of quality. Analyzing these variables, it appears that the length of stay and the number of participants are not statistically significant for the purchase price, showing that the mode of bidding does not appear as determinant of efficiency. Since the dummy showed positive effect of quality on the acquisition of property.